Extracorporeal shockwave therapy (ESWT) – First choice treatment of fracture non-unions?. (December 2015) - Schaden, Wolfgang; Mittermayr, Rainer; Haffner, Nicolas; Smolen, Daniel; Gerdesmeyer, Ludger; Wang, Ching-Jen
Abstract: Fracture non-unions are still a challenging problem in orthopedics. The treatment of non-unions remains highly individualized, complex, and demanding. In most countries the surgical approach with debridement of the non-union gap, anatomical reduction and appropriate osteosynthesis along with autologous bone grafting is considered as the standard of care. One of the very first non-urologic applications of extracorporeal shockwave treatment (ESWT) concerned non-healing fractures. Since the early 1990ties the knowledge of the working mechanism has increased enormously. The purpose of this review article is to demonstrate by peer-reviewed literature in conjunction with our own experiences that ESWT can be an efficient, non-invasive, almost complication-free and cost effective alternative to surgical treatment of non-healing fractures. Highlights: Non-healing fractures (pseudarthroses, non-unions) still are a challenging problem in orthopedics. ESWT is a non-invasive procedure that achieves comparable results to surgical approaches. Complications associated with ESWT are on rare occasions and minimal if present. Peer-reviewed literature shows excellent results with medium/high energy focused ESWT, with faster return to competition and athletic activity.